Nomophobia among nursing students: prevalence and associated factors - Marzeyeh Aslani; Narges Sadeghi; Maryam Janatolmakan; Shahab Rezaeian; Alireza Khatony (Scientific Reports)
Abstract Nomophobia, or the fear of being without a mobile phone, has been linked to negative impacts on the physical, psychological, and academic well-being of students, including nursing students. While the prevalence of nomophobia and its associated factors vary across studies, limited research has focused on nursing students in Hamedan-Iran. This study aimed to determine the prevalence of nomophobia and its related factors among nursing students in Hamedan Province. A cross-sectional study was conducted among 407 nursing students recruited using convenience sampling. Data were collected through the Nomophobia Questionnaire (NMPQ). Statistical analyses, including descriptive statistics, independent t-tests, one-way ANOVA, Scheffé post-hoc tests, and Multiple linear regression, were performed using STATA-14 software to determine the prevalence of nomophobia and identify factors associated with nomophobia among nursing students. Nursing students’ mean total nomophobia score was 73.8 ± 23.7 (out of 140). A substantial proportion (72%) experienced moderate to severe nomophobia. Nomophobia severity was significantly associated with educational level, grade point average, smartphone checking frequency, daily internet usage, and primary phone use (academic vs. non-academic). Educational level, grade point average, and smartphone checking frequency emerged as significant predictors of nomophobia. The present study reveals a high prevalence of nomophobia among nursing students. Given the detrimental impact of nomophobia on physical and mental health, as well as academic performance, there is a pressing need for targeted interventions. Raising awareness about the adverse consequences of excessive smartphone use and providing accessible counseling and psychological support services can be effective strategies to mitigate the negative effects of nomophobia in this population.